Illustrated Guide for the Disposal of Chemicals Used in the Illicit Manufacture of Drugs - United Nations Office on Drugs; Crime (United Nations, 2018)
The present illustrated disposal guide has been developed to support the implementation of the Guidelines and the principles of environmentally-responsible disposal for remote locations, where waste management infrastructure and expert technical support may not be available and where immediate management of seized chemicals is required to reduce unacceptable risk to people, communities and the environment.